R&D and productivity in OECD firms and industries: A hierarchical meta-regression analysis - Mehmet Ugur; Edna Solomon; Francesco Guidi; Eshref Trushin (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Effects of R&D investment on frim/industry productivity have been investigated widely thanks to pioneering contributions by Zvi Griliches and others in late 1970s and early 1980s. We aim to establish where the balance of the evidence lies and what factors may explain the variation in the research findings. Using 1,258 estimates from 65 primary studies and hierarchical meta-regression models, we report that the average elasticity and rate-of-return estimates are both positive, but smaller than those reported in prior narrative reviews and meta-analysis studies. We discuss the likely sources of upward bias in prior reviews, investigate the sources of heterogeneity in the evidence base, and discuss the implications for future research. Overall, this study contributes to existing knowledge by placing the elasticity and rate-of-return estimates under a critical spot light and providing empirically-verifiable explanations for the variation in the evidence base.
Keywords: D24; O30; O32; C49; 330; R&D; knowledge capital; productivity; meta-analysis; R&D; Productivity; Knowledge capital; Meta-analysis